The priority reference of the Educational Inspection model in the Spanish State. Comparative study and inference of challenges - Secadura Navarro, Tomás; Barbero Alcalde, Ana María; Úbeda-Portugués Ávila, Gema; Del Saz Ortega Villaizan, Antonio Jesús (Avances en Supervisión Educativa, 2024)
The article presents the research that has been carried out on the regulatory corpus referring to the work plans and general action plans of the educational inspection (EI), in the Spanish State. The object of study is to determine what is the central reference of the EI in its institutional action. The qualitative methodology, typical of descriptive-comparative studies, and the hemerographic technique for the analysis of comparative legislation are used. The inquiry method has three main phases. It starts from the technical and prior definition of the categorization of nine types of activities of the Inspection, together with the design of a catalog of ten references to be investigated. Afterwards, the EI activities of each educational Administration are recorded, based on the references or areas grouping them, and they are computed and tabulated to deduce the linking percentages between the type of activities and the reference that associates them. Based on those figures and regional values, the global context for the entire Spanish State is assessed and calculated. The analysis of characteristics of action plans and the exploitation of research data allows us to empirically obtain the scale of references that currently articulate the EI, as well as drawing conclusions and formulating proposals on challenges and responses for the 21st century.